ESG Indices, Sustainable Practices and Strategic Competitiveness within the Modern Business Landscape - Sun, Lee Peng; Syriac, Nellikunnel (INTI International University, 2024)
This paper undertakes the arduous task of examining the accuracy and relevance of a statement lacking clear benchmarks. The assertion posits that Environmental, Social and Governance (ESG) indices is indispensable not just for assessing a company’s sustainability efforts, but also enhancing its competitive edge. Through analysis of existing literature, frameworks, and empirical evidence, this article elucidates the nuances inherent in the link between ESG indices, sustainable practices, and strategic competitiveness within the modern business landscape. To accomplish this, the paper adopts a structured approach, dissecting the statement into its constituent components to discern the key points concerning ESG. It intends to challenge the notion of ESG as an indispensable tool in measuring sustainability, while also evaluating relevant initiatives and potential impacts. Furthermore, the article explores the extent to which indices truly function as significant tools, addressing societal and environmental issues while offering pathways for corporate success beyond conventional business performance metrics.